2020
DOI: 10.3846/ijspm.2020.11544
|View full text |Cite
|
Sign up to set email alerts
|

A House Price Valuation Based on the Random Forest Approach: The Mass Appraisal of Residential Property in South Korea

Abstract: Mass appraisal is the standardized procedure of valuing a large number of properties at the same time and is commonly used to compute real estate tax. While a hedonic pricing model based on the ordinary least squares (OLS) linear regression has been employed as the traditional method in this process, the stability and accuracy of the model remain questionable. This paper investigates the features of a house price predictor based on the Random Forest (RF) method by comparing it with that of a conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 46 publications
1
71
0
2
Order By: Relevance
“…To provide a value estimate of a building, it is also possible to use the hedonic regression model, which has already been examined many times, or also for specific buildings, data on their repeated sales [5]. The random forest method has proven to be a useful complementary tool to capture the complexity and nonlinearity of the entire set of buildings that is the subject of the valuation [6]. Using an interoperable data model for the valuation of land intended for building, national geographic data infrastructures can be extended, which could lead to mass valuation when using machine learning as a numerical processor.…”
Section: Literary Researchmentioning
confidence: 99%
“…To provide a value estimate of a building, it is also possible to use the hedonic regression model, which has already been examined many times, or also for specific buildings, data on their repeated sales [5]. The random forest method has proven to be a useful complementary tool to capture the complexity and nonlinearity of the entire set of buildings that is the subject of the valuation [6]. Using an interoperable data model for the valuation of land intended for building, national geographic data infrastructures can be extended, which could lead to mass valuation when using machine learning as a numerical processor.…”
Section: Literary Researchmentioning
confidence: 99%
“…Generic applications of real estate market performance appraisals highlight adoptions of weighted appraisal models, random forest approach, hedonic models, genetic algorithm models, artificial intelligence and multicriteria analysis (Abidoye & Chan, 2017;Braun et al, 2020;Hong et al, 2020;Morano et al, 2018;Tajani et al, 2017;Tajani et al, 2020). In light of the scope of the study which focused on the residential and commercial real estate market in Port Harcourt, Nigeria, a benchmarking of these performance appraisal frameworks may not be apposite in view of the data constructions deficit encumbering the market.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al (2020) showed better predictive performance of machine learning-based predictor (property price predictor based on the Random Forest method) compared to the hedonic pricing model (ordinary-least square-based property price predictor) [12]. Moreno-Izquierdo et al (2018) compared the performance of the Artificial Neural Network (ANN) and hedonic regression model for the price optimization procedure [7].…”
Section: -Introductionmentioning
confidence: 99%